Temperature Dependence of the Spontaneous Polarization Near the Ferroelectric-Paraelectric Transition in NaNO2 - Kuşoğlu Sarıkaya C.; Yurtseven H. (High Temperature Materials and Processes, 2013)
The paraelectric-ferroelectric transition in NaNO2 is studied using the Levanyuk-Sannikov and the mean field models which we have developed here. From both models, the temperature dependence of the spontaneous polarization is derived and is fitted to the experimental data from the literature.